2008
DOI: 10.2478/s11536-008-0009-y
|View full text |Cite
|
Sign up to set email alerts
|

The effects of nocturnal dipping on cardiovascular outcomes and proteinuria in essential hypertensive patients

Abstract: AbstractIndividuals who do not have a 10% to 20% reduction in blood pressure (BP) during the night are known as ‘nondippers’. Non-dipping patterns in hypertensive patients have been shown to be associated with an excess of target organ damage and other adverse outcomes. The present study was designed to investigate the relationship between nocturnal BP pattern, defined on the basis of the ambulatory blood pressure monitoring (ABPM) recording, and cardiac and renal target organ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…BP measurements without a fall in nocturnal BP are called non-dipping and with a fall in nocturnal BP is called dipping. 8 Non-dipper patients with essential hypertension are prone to some diseases like left ventricular hypertrophy and stroke probably because of exposing to higher BP levels for 24 h. 8,9 Excessive lowering of BP levels in dipping patients also increase risk for some diseases like cardiac ischemia and silent cerebrovascular damage. [10][11][12][13] Color Doppler imaging is a non-invasive and reproducible imaging method.…”
Section: Introductionmentioning
confidence: 99%
“…BP measurements without a fall in nocturnal BP are called non-dipping and with a fall in nocturnal BP is called dipping. 8 Non-dipper patients with essential hypertension are prone to some diseases like left ventricular hypertrophy and stroke probably because of exposing to higher BP levels for 24 h. 8,9 Excessive lowering of BP levels in dipping patients also increase risk for some diseases like cardiac ischemia and silent cerebrovascular damage. [10][11][12][13] Color Doppler imaging is a non-invasive and reproducible imaging method.…”
Section: Introductionmentioning
confidence: 99%
“…Also the urinary protein excretion increase was higher in the non-dipper group than in the dipper group. In Yusuf Selcoki et al [13] study the spot urine creatinine ratio was significantly higher in the non-dipper group. In our study, we found that mean spot protein creatine ratio in dippers was 0.17 and in non-dippers 3.88 (p=0.08).…”
Section: Discussionmentioning
confidence: 87%
“…Recent results have indicated that an increased risk for SAHS is highly prevalent when assessed by a special Berlin questionnaire, and it is frequently associated with resistant hypertension [38]. ABPM should be evaluated in patients with hypertension to assess and prevent risk of morbidity and mortality [39]. In patients with sleep apnea.…”
Section: 1mentioning
confidence: 99%